Review of detection frequency and type of synthetic cannabinoids in herbal compounds analyzed by Istanbul Narcotic Department of the Council of Forensic Medicine, Turkey - GÜLHAN, REZZAN (ELSEVIER SCI LTD, 2013)
In recent years, synthetic cannabinoids have been frequently observed in seized materials all over the world. This new generation of designer drugs, mixed with herbal substances, is also known as Herbal Highs or Legal Highs. There are many articles about the history, type and pharmaco-chemical properties of synthetic cannabinoids in the literature; however the number of articles about the frequency of their detection is limited. In this study, we evaluated the type and detection frequency of synthetic cannabinoids in Istanbul and its surrounding area. The reports of the Council of Forensic Medicine-Istanbul Narcotic Department were retrospectively reviewed for the presence of synthetic cannabinoids in herbal compounds sent by the judicial authorities between August 01, 2010 and March 31, 2012. Among 1200 herbal compounds, 1179 of them (98.3%) contained synthetic cannabinoids. Twenty-one samples (1.7%) had other psychoactive substances. The analysis of 1179 samples showed that JWH-018 was present in 1172 (99.4%) of the samples. JWH-081 was found in 777 samples (65.9%) together with JWH-018. Samples had different package names. Bonzai Aromatic Potpourri (n = 755; 64.0%) and Bonzai Plant Growth Regulator (n = 316; 26.8%) were the most common product names amongst the herbal products in this study. It is clear from the present study and previous studies that brand name of synthetic cannabinoids that dominate the market exhibit regional differences as to the type and detection frequency of synthetic cannabinoids and the content of herbal highs packages. The number and diversity of synthetic cannabinoid compounds have increased dramatically in the drug market in recent years. New, different, potent derivatives appear on the market, almost every clay and this presents important problems that need to be solved by scientists and judicial authorities working to prevent their harm. These problems include the limited knowledge about their frequency, the lack of analytical data and reference standards for analysis of these new derivates, the lack of information on their toxic effects, and information about the metabolism and metabolites for toxicological analysis in human subjects. (c) 2013 Elsevier Ltd and Faculty of Forensic and Legal Medicine. All rights reserved.
Keywords: Synthetic cannabinoids; Herbal highs; Legal highs; New designer drugs; Frequency; Types; PHARMACOLOGY; SYSTEM; UNION; SPICE